Characterization of The Process of Making Golden Sea Cucumber (Stichopus hermanii) Simplicia - Sumaryani Sumaryani; Wintari Taurina; Mohamad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
haracterization is the first step to ensuring uniformity of drug quality. Golden sea cucumber (Stichopus hermanii) is one of the natural ingredients that has efficacy as a wound-healing drug. This study aims to determine the characterization of the process of making golden sea cucumber Simplicia originating from Pelapis Island, Kayong Utara Regency, as raw materials for wound healing drug preparations. Simplicia was characterized biologically including morphology and habitat, physically including organoleptic, moisture content, ash content, and acid insoluble ash content, and chemically including phytochemical screening and protein content. Simplicia making process consists of sample collecting, wet sorting, washing, boiling, smoking, first drying, chopping, and second drying, dry sorting, packaging, and storage.% yield obtained is 8,43%. The results of the characterization were that fresh golden sea cucumbers had a yellow body, long of 31 cm, bodyweight of 1.3 kg, body thickness of 5 cm, and live in rock and coral areas with a sea depth of about 10-15 meters. Simplicia are brownish yellow, the distinctive smell of sea cucumbers, salty taste, and thin slices. The water content, ash content, acid insoluble ash content, and protein of Simplicia were 9.8%, 13.77%, 0.20%, and 36.1%, respectively. The outcome of phytochemical screening showed that Simplicia qualitatively contained alkaloids, saponins, and triterpenoids.